Dividend payout policies of politically connected firms: Evidence from Malaysia - Rozaimah Zainudin; Karren Lee-Hwei Khaw (Borsa İstanbul Review, 2021)
This study expounds on the debate regarding dividend payouts for different types of politically tied firms in Malaysia. We recognize the heterogeneity of political ties of politically connected firms (PCFs) by government-linked companies (GLCs) and non-GLC PCFs. The results show that PCFs are positively related to dividend payouts and that PCFs, specifically GLCs, pay higher dividends than their counterparts. Additionally, our results demonstrate that high- and low-levered GLCs consistently pay higher dividends than non-GLC PCFs and non-PCFs. These findings imply that GLCs implement special dividend policies, and therefore, a high GLC payout might not be indicative of actual performance. In brief, shareholders and potential investors should be cautious in interpreting firm payout signals.
Keywords: G23; G32; G34; 330; Politically connected firms; Government-linked companies; Dividend payout policy; Signaling theory